2023
DOI: 10.1371/journal.pgph.0001250
|View full text |Cite
|
Sign up to set email alerts
|

Perceived coercion, perceived pressures and procedural justice arising from global lockdowns during the COVID-19 pandemic: A scoping review

Abstract: This aim of this scoping review is to map what is known about perceived coercion, perceived pressures and procedural justice within the context of the general population’s experience of ‘lockdowns’ imposed by governments worldwide in response to the increased transmission of COVID-19. Arksey & O’Malley’s (2005) framework for conducting scoping reviews was chosen. A sensitive search strategy was devised and conducted using PubMed, Scopus, and Web of Science using the following search terms: (adherence OR ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Participants spoke of experiencing anxiety and low mood linked to lockdown and a sense of ‘entrapment’ in this and previous studies [ 8 , 21 ]. Unlike a previous scoping review by the authors, perceived pressure in the form of social norms and perceived control in the form of conspiracy theories did not feature within this study [ 7 ].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Participants spoke of experiencing anxiety and low mood linked to lockdown and a sense of ‘entrapment’ in this and previous studies [ 8 , 21 ]. Unlike a previous scoping review by the authors, perceived pressure in the form of social norms and perceived control in the form of conspiracy theories did not feature within this study [ 7 ].…”
Section: Discussionmentioning
confidence: 57%
“…A subsequent national lockdown took effect from 5th November for four weeks merging into a three then four ‘tiered’ system before another national lockdown on 6th January 2021 and phased return between March and July 2021. A recent scoping review on perceived coercion within the context of the COVID-19 pandemic, gave an early indication that many individuals met lockdowns with an initial acceptance that decreased over time as a sense of intrusiveness by authorities emerged worldwide [ 6 , 7 ]. It also highlighted a link between low perceived control and greater depressive and anxious symptomatology [ 8 ], As found in the scoping review, it remains unclear as to who perceives lockdowns as more coercive and procedurally unjust and whether there are specific individual experiences and characteristics that increase the likelihood of these perceptions and of potentially dissatisfaction and disengagement with restrictions [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these contributions, our scoping review highlights limitations in the ways that FBOs' contributions are not well-documented. The findings of this scoping review, echoing others [213], point to a critical need to further evaluate the impact of initiatives.…”
Section: Plos Global Public Healthmentioning
confidence: 56%
“…A scoping review showed that participants were more likely to accept lockdown when there was a perception of risk from the disease and when communications were articulated by authorities in whom they trusted ( Ranieri et al, 2023 ). In Brazil, the federal government showed a notoriously denialist stance toward the pandemic that discouraged mask wearing and social distancing ( Idrovo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another factor observed in the anti-lockdown Cluster was greater sadness over the possibility of lockdown and a feeling of deprivation of freedom. The relationship between perceived coercion and lockdown has been assessed in some studies, and a review has suggested that people who feel less control over their lived experiences suffered greater anxiety, depression, and a feeling of imprisonment ( Ranieri et al, 2023 ). Another factor potentially contributing to greater sadness in the anti-lockdown group may suggest suffering linked to neoliberal ideologies that can contribute to the anguish many people experienced during the pandemic.…”
Section: Discussionmentioning
confidence: 99%